High-density and low-temperature curing conductive silver paste and preparation method thereof

By optimizing the proportion of silver powder and using low-boiling solvents and cashew phenol-based epoxy resins, the problem that existing conductive silver paste is difficult to improve at the same time in density, bending resistance and low-temperature curing is achieved, and high-density and low-temperature curing is achieved and conductive silver paste with high bending resistance significantly improves conductive performance and production efficiency.

CN119132696APending Publication Date: 2024-12-13HEXENE ELECTRONIC TECH (JIANGSU) CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411508415.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing conductive silver paste is difficult to achieve low-temperature curing while improving density and bending resistance, and the conductive performance is insufficient and the cost is high.

Method used

Three different sizes of spherical silver powder are used to optimize the proportion of silver powder through spherical close packing, combining low-boiling solvents and cashew phenol-based epoxy resins to reduce the amount of bonding phase and improve the space utilization and conductivity of silver powder.

Benefits of technology

Conductive silver paste with high density, low temperature curing and high bending resistance has been achieved, which significantly improves the conductive performance and production efficiency and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119132696A_ABST
    Figure CN119132696A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electronic information material science, and particularly relates to a preparation method of high-density and low-temperature curing conductive silver paste. The conductive silver paste is obtained by compounding three kinds of spherical silver powder with different sizes according to a silver powder proportion calculated in a sphere close packing mode, compounding the silver powder with an organic carrier, a solvent and an auxiliary agent, and curing at 120-140 DEG C. According to the invention, a spherical silver powder stacking model based on three fixed spherical silver powder sizes and highest density is constructed for compounding to improve the compactness and the conductivity, an organic solvent with a boiling point of 120-140 DEG C is preferably selected as a solvent phase to reduce the curing temperature, the preparation process is optimized, the nano silver powder added firstly is used as an anti-settling agent, and the nano silver powder added firstly is used as an anti-settling agent; the stability of the system is improved; aiming at the problems of low resin content and poor bending resistance of high-density silver paste, cardanol-based epoxy resin with a tough side chain is selected as an additive, a novel silver paste material with high bending resistance, high density and low-temperature curing is successfully prepared, and the comprehensive performance of the novel silver paste material is far better than that of traditional silver paste of the same type.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electronic information materials, and in particular to a high-density, low-temperature curing composite conductive silver paste and a preparation method thereof. Background Art

[0002] With the rapid development of the 5G information age, the development of industries such as artificial intelligence, big data and flexible electronics, conductive silver paste, as a vital conductive adhesive material, is increasingly used in the fields of electronic information and energy. Conductive silver paste usually consists of silver powder as the conductive phase, which is evenly dispersed in an organic carrier composed of a solvent, a thickening phase and an additive. When used, the conductive silver paste must first be applied to the surface of the substrate. After drying and removing the solvent, the conductive silver paste is solidified, and the silver powder is fixed to the surface of the substrate by the adhesive phase to form a continuous coating material. Among them, the silver powder as the conductive phase is connected into a network by the adhesive phase resin, and the conduction between the silver powder particles is achieved through the tunneling effect of electrons. The higher the density of the silver powder particles and the thinner the thickness of the organic layer between the particles, the higher the conductivity. In order to increase the density of the silver paste and improve the conductive performance, researchers have found that compounding silver powders of different sizes is an effective way to increase the density. Zhao Weiwei, Xie Senpei and others (patent number CN117324632A) proposed a mixed silver powder that combines 0.5-2μm flake silver powder and 100-800nm ​​spherical silver powder for the preparation of conductive paste. Although this mixed silver powder design can improve density, the conductivity of the patented product is still relatively insufficient. The reason is that the patent does not accurately configure the size and dosage to achieve the maximum space utilization of the silver powder inside the silver paste. In theory, it is necessary to match silver powder of various sizes and use a precise dense stacking calculation to maximize the stacking density.

[0003] At the same time, the bonding phase plays a dual role of fixing the silver powder on the substrate surface and bonding the silver powder to the silver powder network. The higher the bonding phase content, the better the mechanical properties of the conductive silver paste, such as anti-bending performance and adhesion. In addition, before curing, the bonding phase also serves to increase the viscosity of the organic phase and reduce the sedimentation of the silver powder. It usually needs to be used in combination with solvents, additives, etc. to obtain a conductive silver paste material with good stability.

[0004] In addition to conductivity and mechanical properties, curing temperature is also an important performance parameter of conductive silver paste. The curing temperature is mainly determined by the boiling point of the solvent. The commonly used solvents for conductive silver paste currently include dibasic acid ester DBE, terpineol diethylene glycol butyl ether, ethylene glycol, diethylene glycol ethyl ether acetate, diethylene glycol ethyl ether, etc., and their boiling points are generally 180-220°C. With the expansion of the application of conductive silver paste in the field of flexible electronics and other fields, the demand for high-performance low-temperature curing silver paste is increasing. Although the selection of low-boiling point solvents can easily reduce the curing temperature of conductive silver paste, the viscosity of low-boiling point solvents is generally low, which leads to the need to increase the content of the adhesive phase to increase the viscosity of the organic carrier, which will lead to insufficient performance of the conductive silver paste; although the use of a high-viscosity adhesive phase can increase the viscosity of the organic carrier, it will increase the brittleness of the conductive coating after curing and reduce its anti-bending performance.

[0005] Based on the above mechanism, researchers have carried out a lot of work and developed a series of low-temperature curing conductive silver pastes by optimizing solvents, adhesive phases, silver paste ratios, etc. For example, Song Tao et al. (patent number CN105679407A) proposed to use 30-600nm silver powder to prepare conductive silver paste. Due to the small size of nano silver powder, the sedimentation performance is significantly reduced in low-viscosity and low-boiling point solvents. The silver paste silver powder mass accounts for 70% to 80%, the silver paste curing temperature is 50 to 120°C, and the resistivity is 0.02 to 0.1Ω·cm. However, the nano silver powder system and the micron silver powder system phase change, the organic phase-silver powder interface is greatly increased, resulting in insufficient conductivity, and the cost is also greatly increased. Lan Yubin et al. (patent number CN102254586A) proposed to use silver powder with a size of 5.5 to 10 μm to prepare a conductive silver paste with low curing temperature and low cost. By optimizing the resin in the silver paste, that is, mixing polyurethane and chloroacetic resin in proportion and increasing the content of the polymer resin carrier, the silver paste has a silver powder mass ratio of 40% to 45%, and the curing temperature of the silver paste is 80 to 120°C. However, the excessively high polymer resin carrier content and the low proportion of silver powder result in a low internal space utilization rate of the silver powder in the silver paste, a decrease in the density of the silver paste, and insufficient conductive performance. Summary of the invention

[0006] Purpose of the invention: In order to solve the problem that density, bending resistance and low curing temperature cannot be improved at the same time in the existing conductive silver paste preparation technology, and to effectively improve the comprehensive performance of the conductive silver paste, the present invention provides a high bending resistance, high density, low temperature curing composite conductive silver paste and a preparation method thereof.

[0007] The present invention provides a high-bending-resistance, high-density, low-temperature-curing composite conductive silver paste and a preparation method thereof to solve the technical problem. The specific technical scheme is as follows:

[0008] A high-density, low-temperature curing conductive silver paste comprises the following components in proportion by weight:

[0009] A. Spherical silver powder with a particle size of 300nm to 2μm: 5 to 15 parts;

[0010] B. Spherical silver powder with a particle size of 5 to 10 μm: 10 to 25 parts;

[0011] C. Spherical silver powder with a particle size of 20 to 30 μm: 30 to 50 parts;

[0012] D. Organic solvent: 15 to 30 parts;

[0013] E. Additives: 0.1 to 3 parts of leveling agent, 0.1 to 3 parts of defoaming agent, 1 to 3 parts of thixotropic agent;

[0014] F. Thickener: 1 to 3 parts;

[0015] G. Coupling agent: 1 to 5 parts;

[0016] H. Binder: 1 to 5 parts.

[0017] The weight ratio of the spherical silver powder with a particle size of 300 nm to 2 μm, the spherical silver powder with a particle size of 5 to 10 μm, and the spherical silver powder with a particle size of 20 to 30 μm is 1:1 to 2:1 to 9. Preferably, the weight ratio is 9:17:74.

[0018] Wherein, the binder comprises cardanol-based epoxy resin, and the mass percentage of the cardanol-based epoxy resin in the binder is 20%-50%, preferably 40%.

[0019] The adhesive further comprises a mixture of any one or more of epoxy resin E51, acrylic resin, polyamino resin, epoxy-modified polyester resin, epoxy polyphenol resin or polyurethane resin; preferably epoxy resin E51.

[0020] The organic solvent has a boiling range of 120-140° C. and is preferably a mixture of any one or more of butyl acetate, ethylene glycol methyl ether, propylene glycol methyl ether acetate, diethyl carbonate, cyclohexanone, 4-methyl-2-pentanone and ethylene glycol ethyl ether acetate. More preferably, diethyl carbonate is used.

[0021] Wherein, the leveling agent is a mixture of any one or more of polydimethylsiloxane, BYK-381 and polyacrylate; BYK-381 is preferred.

[0022] The defoamer is BYK-A530 or polyether-modified siloxane, or a mixture of the two; BYK-A530 is preferred.

[0023] The thixotropic agent BYK-410.

[0024] Wherein, the coupling agent is a mixture of any one or more of KH550, KH560, KH570, KH792 and DL602; preferably KH560.

[0025] The thickener is a mixture of any one or more of ethyl cellulose, polyvinyl alcohol, epoxy resin E51, polyvinyl butyral ester and polyisobutylene, preferably ethyl cellulose.

[0026] Wherein, the high density is 2.3-3 g / cm 3 ; The low temperature curing has a curing temperature of 120-140°C, preferably 126°C.

[0027] In a second aspect, the present invention provides a method for preparing the high-density, low-temperature curing conductive silver paste described in the first aspect, comprising the following steps:

[0028] (1) Preparation of organic carrier solution: After fully mixing the organic solvent and thickener in the formula amount, adding the auxiliary agent and mixing evenly, and then adding the coupling agent to obtain the organic carrier solution;

[0029] (2) Preparation of conductive silver paste: Add a binder to the organic carrier solution and mix well to obtain a resin solution, add spherical silver powder to the resin solution in order of particle size, and disperse at high speed to obtain a conductive silver paste.

[0030] Wherein, in step (1), the organic solvent and thickener are mixed and stirred in a water bath at 50-90°C until the thickener is completely dissolved; after adding the auxiliary agent, they are stirred in a water bath at 40-80°C for 1.5-4h. Preferably, the organic solvent and thickener are mixed and stirred in a water bath at 60°C until the thickener is completely dissolved; after adding the auxiliary agent, they are stirred in a water bath at 60°C for 2-4h until the organic carrier becomes a transparent and uniform liquid. After the liquid is cooled to room temperature, it is vacuum-defoamed and bottled for later use.

[0031] Wherein, in step (2), the organic carrier solution is stirred and mixed in a water bath at 50-80°C after adding a binder; the high-speed dispersion is performed at a speed of 1000-1200 rpm for 0.5-3 hours. Preferably, the organic carrier solution is stirred and mixed in a water bath at 60°C after adding a binder; the high-speed dispersion is performed at a speed of 1000-1200 rpm for 1-2 hours. Further preferably, spherical silver powder is added in order of size from small to large.

[0032] Beneficial effects: Preparation effects and advantages of the present invention:

[0033] In order to achieve the preparation of high-bending, high-density, low-temperature curing conductive silver paste, this patent proposes 1. Using three different sizes of spherical silver powders to calculate the proportion of different silver powders through spherical close packing, maximize the space occupancy of silver powder inside the system, and improve the density and conductivity of the conductive silver paste; 2. Reduce the curing temperature of the silver paste by using low-boiling point solvents; 3. Reduce the amount of adhesive phase by introducing a small amount of nano silver powder as an anti-settling agent; 4. Introduce low-viscosity, high-toughness cardanol-based epoxy resin to partially replace the traditional high-viscosity and high-brittle resin adhesive phase, and improve the bending resistance without increasing the amount of adhesive phase. Based on the above mechanism, this patent successfully prepared a new low-temperature curing conductive silver paste product with comprehensive performance far exceeding that of existing silver pastes.

[0034] The present invention innovatively applies a diversified close packing strategy for metal particles and designs spherical silver powder packing models covering different sizes. These models significantly optimize the space utilization efficiency inside the silver powder, allowing the silver paste material to achieve a higher density level. Based on this optimization, the present invention successfully developed a new type of silver paste material with excellent conductive properties.

[0035] The present invention innovatively introduces a new type of high-efficiency organic solvent by carefully selecting the types of solvents. The solvent has excellent solubility, compatibility with silver powder and binder, and low boiling point. Using this solvent, the present invention successfully developed a new type of conductive silver paste product with significantly reduced curing temperature and excellent performance. This achievement optimizes the production process, significantly improves the overall quality and performance of the product, reduces the cost of silver paste preparation, and improves the efficiency of silver paste preparation. The silver paste prepared by the present invention has high bending resistance, high density and low-temperature curing, and has extremely high application prospects, especially in the field of printed circuits. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0037] Figure 1 Optical photos of micro-nano silver powders of different sizes; Figure 1 A is an optical photograph of spherical silver powder with a particle size of 300nm to 2μm. Figure 1 B is an optical photograph of spherical silver powder with a particle size of 5 to 10 μm. Figure 1 C is an optical photograph of spherical silver powder with a size of 22 to 30 μm.

[0038] Figure 2 This is the conductive silver paste image prepared. Figure 2 A is the conductive silver paste prepared without adding nano silver powder as described in Example 6, Figure 2 B is the conductive silver paste prepared by adding nano silver powder in Example 2. DETAILED DESCRIPTION

[0039] The present invention can be better understood with reference to the following examples.

[0040] The present invention will be described in further detail below in conjunction with specific examples, but the embodiments of the present invention are not limited thereto. Those skilled in the art will recognize that the chemical reactions described in the present invention can be used to appropriately prepare many other compounds of the present invention, for example, other methods for preparing the compounds of the present invention are considered to be within the scope of the present invention by making some conventional modifications to the reaction conditions of the present invention.

[0041] In the following examples, the cardanol-based epoxy resin is cardanol-based epoxy resin PLR 602A, which was purchased from Changshu Naisu Biomaterial Technology Co., Ltd.

[0042] In the following examples, the optical photographs of the different sizes of micro-nano silver powders used are as follows: Figure 1 shown.

[0043] Example 1

[0044] Prepare the required raw materials according to the following weight ratio:

[0045] A. Spherical silver powder with particle size of 300nm~2μm: 2.925g

[0046] B. Spherical silver powder with particle size of 5-10 μm: 5.525 g

[0047] C. Spherical silver powder with a particle size of 20 to 30 μm: 24.05 g

[0048] D. Organic solvent with boiling range of 120-140°C: 11.475 g

[0049] E. Additives: leveling agent 0.135g, defoaming agent 0.135g, thixotropic agent 1.08g

[0050] F. Thickener: 0.675g

[0051] G. Coupling agent: 2g

[0052] H. Binder: 1g

[0053] Wherein, the organic solvent is diethyl carbonate.

[0054] Among them, the leveling agent is BYK-381, the defoaming agent is BYK-A530, the thixotropic agent is BYK-410, and the thickener is ethyl cellulose.

[0055] Among them, the coupling agent is KH560.

[0056] The binder is a mixture of cardanol-based epoxy resin and epoxy resin E51 in a mass ratio of 1:1.

[0057] The specific preparation method is carried out according to the following steps:

[0058] (1) Preparation of organic carrier

[0059] Use an electronic analytical balance to weigh 11.475g of organic solvent diethyl carbonate and 0.675g of thickener ethyl cellulose in a ratio of 17:1 and put them into a beaker. Stir in a constant temperature 60℃ water bath until the thickener is completely dissolved. Then add the leveling agent, defoaming agent and thixotropic agent into the beaker in a ratio of 1:1:8, keep stirring in a constant temperature water bath at 60℃ for 1.5 to 3 hours until the organic carrier becomes a transparent and uniform liquid. After the liquid cools to room temperature, add the coupling agent, continue stirring for 5 minutes, vacuum remove bubbles and bottle for later use.

[0060] (2) Preparation of conductive silver paste

[0061] The 300nm-2μm nano-sized spherical silver powder, 5-10μm spherical silver powder and 20-30μm spherical silver powder were compounded and weighed according to the metal stacking method results (according to the three spherical silver powders, the most densely packed method-face-centered cubic stacking method, the proportion of the three silver powders was simulated and calculated, and the metal stacking results were obtained). First, 1g of the above binder was weighed with an electronic analytical balance and added to a beaker, and then the above-prepared organic carrier was added, and the resin solution was obtained by stirring in a constant temperature water bath of 60°C. Finally, the three silver powders prepared above were added to the resin solution in order from small to large in size, and placed in a high-speed disperser for high-speed dispersion at 1000r / min for 1-2 hours. After being dispersed evenly, the prepared conductive silver paste was obtained.

[0062] When preparing the organic carrier, add the binder and stir it after it is completely dissolved. After stirring evenly, add other additives, which is not only conducive to the role of the additives, but also can promote the uniform mixing of the components. After preparing the resin solution, three kinds of spherical silver powders are added in batches according to size from small to large. By introducing a small amount of nano silver powder as an anti-settling agent, the amount of the binder phase is reduced. Use a high-speed grinder to disperse at high speed for 5 minutes, and finally grind the prepared sample in a three-roll grinder, and then vacuum it to remove bubbles to obtain the final high-density composite conductive silver paste.

[0063] By controlling the process, the distribution of particles and the contact state inside the conductive silver paste can be made more uniform, which is more conducive to improving the mechanical properties of the silver paste, such as conductivity and adhesion.

[0064] Example 2

[0065] Prepare the required raw materials according to the following weight ratio:

[0066] A. Spherical silver powder with particle size of 300nm~2μm: 2.925g

[0067] B. Spherical silver powder with particle size of 5-10 μm: 5.525 g

[0068] C. Spherical silver powder with a particle size of 20 to 30 μm: 24.05 g

[0069] D. Organic solvent with boiling range of 120-140°C: 11.475 g

[0070] E. Additives: leveling agent 0.135g, defoaming agent 0.135g, thixotropic agent 1.08g

[0071] F. Thickener: 0.675g

[0072] G. Coupling agent: 2g

[0073] H. Binder: 1g

[0074] Wherein, the organic solvent is diethyl carbonate.

[0075] Among them, the leveling agent is BYK-381, the defoaming agent is BYK-A530, the thixotropic agent is BYK-410, and the thickener is ethyl cellulose.

[0076] Among them, the coupling agent is KH560.

[0077] The binder is a mixture of cardanol-based epoxy resin and epoxy resin E51 in a mass ratio of 2:3.

[0078] The specific preparation method is carried out according to the following steps:

[0079] (1) Preparation of organic carrier

[0080] Use an electronic analytical balance to weigh 11.475g of organic solvent diethyl carbonate and 0.675g of thickener ethyl cellulose in a ratio of 17:1 and put them into a beaker. Stir in a constant temperature 60℃ water bath until the thickener is completely dissolved. Then add the leveling agent, defoamer, and thixotropic agent into the beaker in a ratio of 1:1:8, keep stirring in a constant temperature water bath at 60℃ for 2 to 3 hours until the organic carrier becomes a transparent and uniform liquid. After the liquid cools to room temperature, add the coupling agent, continue stirring for 5 minutes, vacuum remove bubbles and bottle for later use.

[0081] (3) Preparation of conductive silver paste

[0082] 300nm~2μm nano-sized spherical silver powder, 5~10μm spherical silver powder and 20~30μm spherical silver powder are compounded and weighed in a metal stacking method at a ratio of 9:17:74. First, 1g of the above-mentioned binder is weighed with an electronic analytical balance and added into a beaker. Then, the above-prepared organic carrier is added and stirred in a constant temperature water bath of 60°C to obtain a resin solution. Finally, the above-prepared three kinds of silver powder are added to the resin solution in order from small to large in size, and placed in a high-speed disperser for high-speed dispersion at 1000r / min for 1 to 3 hours. After being dispersed evenly, the prepared conductive silver paste is obtained.

[0083] Example 3

[0084] Prepare the required raw materials according to the following weight ratio:

[0085] A. Spherical silver powder with particle size of 300nm~2μm: 2.925g

[0086] B. Spherical silver powder with particle size of 5-10 μm: 5.525 g

[0087] C. Spherical silver powder with a particle size of 20 to 30 μm: 24.05 g

[0088] D. Organic solvent with boiling range of 120-140°C: 11.475 g

[0089] E. Additives: leveling agent 0.135g, defoaming agent 0.135g, thixotropic agent 1.08g

[0090] F. Thickener: 0.675g

[0091] G. Coupling agent: 2g

[0092] H. Binder: 1g

[0093] Wherein, the organic solvent is diethyl carbonate.

[0094] Among them, the leveling agent is BYK-381, the defoaming agent is BYK-A530, the thixotropic agent is BYK-410, and the thickener is ethyl cellulose.

[0095] Among them, the coupling agent is KH560.

[0096] The binder is a mixture of epoxy resin E51 and cardanol-based epoxy resin in a mass ratio of 7:3.

[0097] The specific preparation method is carried out according to the following steps:

[0098] (1) Preparation of organic carrier

[0099] Use an electronic analytical balance to weigh 11.475g of organic solvent diethyl carbonate and 0.675g of thickener ethyl cellulose in a ratio of 17:1 and put them into a beaker. Stir in a constant temperature 60℃ water bath until the thickener is completely dissolved. Then add the leveling agent, defoamer, and thixotropic agent into the beaker in a ratio of 1:1:8, keep stirring in a constant temperature water bath at 60℃ for 2 to 4 hours until the organic carrier becomes a transparent and uniform liquid. After the liquid cools to room temperature, add the coupling agent, continue stirring for 5 minutes, vacuum remove bubbles and bottle for later use.

[0100] (2) Preparation of conductive silver paste

[0101] 300nm~2μm nano-sized spherical silver powder, 5~10μm spherical silver powder and 20~30μm spherical silver powder are compounded and weighed in a metal stacking method at a ratio of 9:17:74. First, 1g of the binder is weighed with an electronic analytical balance and added into a beaker. Then, the prepared organic carrier is added and stirred in a constant temperature water bath of 60°C to obtain a resin solution. Finally, the three silver powders prepared above are added to the resin solution in order from small to large in size, and placed in a high-speed disperser for high-speed dispersion at 1500r / min for 1~2 hours. After being dispersed evenly, the prepared conductive silver paste is obtained.

[0102] Example 4

[0103] Prepare the required raw materials according to the following weight ratio:

[0104] A. Spherical silver powder with particle size of 300nm~2μm: 2.925g

[0105] B. Spherical silver powder with particle size of 5-10 μm: 5.525 g

[0106] C. Spherical silver powder with a particle size of 20 to 30 μm: 24.05 g

[0107] D. Organic solvent with boiling range of 120℃~140℃: 11.475g

[0108] E. Additives: leveling agent 0.135g, defoaming agent 0.135g, thixotropic agent 1.08g

[0109] F. Thickener: 0.675g

[0110] G. Coupling agent: 2g

[0111] H. Binder: 1g

[0112] Wherein, the organic solvent is diethyl carbonate.

[0113] Among them, the leveling agent is BYK-381, the defoaming agent is BYK-A530, the thixotropic agent is BYK-410, and the thickener is ethyl cellulose.

[0114] Among them, the coupling agent is KH560.

[0115] The binder is a mixture of epoxy resin E51 and cardanol-based epoxy resin in a mass ratio of 4:1.

[0116] (1) Preparation of organic carrier

[0117] Use an electronic analytical balance to weigh 11.475g of organic solvent diethyl carbonate and 0.675g of thickener ethyl cellulose in a ratio of 17:1 and put them into a beaker. Stir in a constant temperature 60℃ water bath until the thickener is completely dissolved. Then add the leveling agent, defoamer, and thixotropic agent into the beaker in a ratio of 1:1:8, keep stirring in a constant temperature water bath at 60℃ for 2 to 3 hours until the organic carrier becomes a transparent and uniform liquid. After the liquid cools to room temperature, add the coupling agent, continue stirring for 5 minutes, vacuum remove bubbles and bottle for later use.

[0118] (3) Preparation of conductive silver paste

[0119] 300nm~2μm nano-sized spherical silver powder, 5~10μm spherical silver powder and 20~30μm spherical silver powder are compounded and weighed in a metal stacking method at a ratio of 9:17:74. First, 1g of the binder is weighed with an electronic analytical balance and added to a beaker. Then, the prepared organic carrier is added and stirred in a constant temperature water bath of 60°C to obtain a resin solution. Finally, the three silver powders prepared above are added to the resin solution in order from small to large in size, and placed in a high-speed disperser for high-speed dispersion at 1500r / min for 1~2 hours. After being dispersed evenly, the prepared conductive silver paste is obtained.

[0120] Example 5

[0121] Prepare the required raw materials according to the following weight ratio:

[0122] A. Spherical silver powder with particle size of 300nm~2μm: 4.875g

[0123] B. Spherical silver powder with particle size of 5-10 μm: 3.575 g

[0124] C. Spherical silver powder with a particle size of 20 to 30 μm: 24.05 g

[0125] D. Organic solvent with boiling range of 120-140°C: 11.475 g

[0126] E. Additives: leveling agent 0.135g, defoaming agent 0.135g, thixotropic agent 1.08g

[0127] F. Thickener: 0.675g

[0128] G. Coupling agent: 2g

[0129] H. Binder: 1g

[0130] Wherein, the organic solvent is diethyl carbonate.

[0131] Among them, the leveling agent is BYK-381, the defoaming agent is BYK-A530, the thixotropic agent is BYK-410, and the thickener is ethyl cellulose.

[0132] Among them, the coupling agent is KH560.

[0133] The adhesive is a mixture of epoxy resin E51 and cardanol-based epoxy resin in a mass ratio of 7:3.

[0134] The specific preparation method is carried out according to the following steps:

[0135] (1) Preparation of organic carrier

[0136] Use an electronic analytical balance to weigh 11.475g of organic solvent diethyl carbonate and 0.675g of thickener ethyl cellulose in a ratio of 17:1 and put them into a beaker. Stir in a constant temperature 60℃ water bath until the thickener is completely dissolved. Then add the leveling agent, defoamer, and thixotropic agent into the beaker in a ratio of 1:1:8, keep stirring in a constant temperature water bath at 60℃ for 2 to 4 hours until the organic carrier becomes a transparent and uniform liquid. After the liquid cools to room temperature, add the coupling agent, continue stirring for 5 minutes, vacuum remove bubbles and bottle for later use.

[0137] (2) Preparation of conductive silver paste

[0138] 300nm~2μm nano-sized spherical silver powder, 5~10μm spherical silver powder and 20~30μm spherical silver powder are compounded and weighed in a metal stacking method at a ratio of 15:11:74. First, 1g of the binder is weighed with an electronic analytical balance and added into a beaker. Then, the prepared organic carrier is added and stirred in a constant temperature water bath of 60°C to obtain a resin solution. Finally, the three silver powders prepared above are added to the resin solution in order from small to large in size, and placed in a high-speed disperser for high-speed dispersion at 1000r / min for 1~2 hours. After being dispersed evenly, the prepared conductive silver paste is obtained.

[0139] Example 6

[0140] Prepare the required raw materials according to the following weight ratio:

[0141] A. Spherical silver powder with particle size of 5-10 μm: 13.0 g

[0142] B. Spherical silver powder with particle size of 20-30 μm: 19.5 g

[0143] C. Organic solvent with boiling range of 120-140°C: 11.475 g

[0144] D. Additives: leveling agent 0.135g, defoaming agent 0.135g, thixotropic agent 1.08g

[0145] E. Thickener: 0.675g

[0146] F. Coupling agent: 2g

[0147] G. Binder: 1g

[0148] Wherein, the organic solvent is diethyl carbonate.

[0149] Among them, the leveling agent is BYK-381, the defoaming agent is BYK-A530, the thixotropic agent is BYK-410, and the thickener is ethyl cellulose.

[0150] Among them, the coupling agent is KH560.

[0151] The binder is a mixture of epoxy resin E51 and cardanol-based epoxy resin in a mass ratio of 7:3.

[0152] The specific preparation method is carried out according to the following steps:

[0153] (1) Preparation of organic carrier

[0154] Use an electronic analytical balance to weigh 11.475g of organic solvent diethyl carbonate and 0.675g of thickener ethyl cellulose in a ratio of 17:1 and put them into a beaker. Stir in a constant temperature 60℃ water bath until the thickener is completely dissolved. Then add the leveling agent, defoamer, and thixotropic agent into the beaker in a ratio of 1:1:8, keep stirring in a constant temperature water bath at 60℃ for 2 to 4 hours until the organic carrier becomes a transparent and uniform liquid. After the liquid cools to room temperature, add the coupling agent, continue stirring for 5 minutes, vacuum remove bubbles and bottle for later use.

[0155] (2) Preparation of conductive silver paste

[0156] 5-10 μm spherical silver powder and 20-30 μm spherical silver powder are weighed in a ratio of 2:3. First, 1 g of the binder is weighed using an electronic analytical balance and added to a beaker. Then, the prepared organic carrier is added and stirred in a constant temperature water bath of 60°C to obtain a resin solution. Finally, the two prepared silver powders are added to the resin solution and placed in a high-speed disperser for high-speed dispersion at 1500 r / min for 1 to 2 hours. After being dispersed evenly, a prepared conductive silver paste is obtained.

[0157] The nano silver paste was prepared by the same preparation process, but no nano silver powder was added in Example 6. The results are as follows: Figure 2As shown in Figure A, the color of the upper layer of the slurry is lighter, while the color of the lower layer is darker, which reflects that most of the spherical silver particles have settled and are mainly concentrated at the bottom of the slurry. In contrast, after adding nano silver powder in Example 2, the conductive silver paste obtained has a more uniform color distribution (as shown in Figure 2). Figure 2 B). This indicates that the addition of nano silver powder helps to improve the sedimentation problem, so that the spherical silver particles no longer have obvious sedimentation, and the stability of the slurry is improved.

[0158] Comparative Example 1

[0159] Prepare the required raw materials according to the following weight ratio:

[0160] A. Spherical silver powder with particle size of 300nm~2μm: 2.925g

[0161] B. Spherical silver powder with particle size of 5-10 μm: 5.525 g

[0162] C. Spherical silver powder with a particle size of 20 to 30 μm: 24.05 g

[0163] D. Organic solvent with boiling range of 180-200°C: 11.475 g

[0164] E. Additives: leveling agent 0.135g, defoaming agent 0.135g, thixotropic agent 1.08g

[0165] F. Thickener: 0.675g

[0166] G. Coupling agent: 2g

[0167] H. Binder: 1g

[0168] Wherein, the organic solvent is dibasic acid ester DBE.

[0169] Among them, the leveling agent is BYK-381, the defoaming agent is BYK-A530, the thixotropic agent is BYK-410, and the thickener is ethyl cellulose.

[0170] Among them, the coupling agent is KH560.

[0171] The adhesive is a mixture of carbophenol-based epoxy resin and epoxy resin E51 in a mass ratio of 2:3.

[0172] The specific preparation method is carried out according to the following steps:

[0173] (1) Preparation of organic carrier

[0174] Use an electronic analytical balance to weigh 11.475g of organic solvent dibasic acid ester DBE and 0.675g of thickener ethyl cellulose in a ratio of 17:1 and put them into a beaker. Stir in a constant temperature 60℃ water bath until the thickener is completely dissolved. Then add the leveling agent, defoamer and thixotropic agent into the beaker in a ratio of 1:1:8, keep stirring in a constant temperature water bath at 60℃ for 2 to 4 hours until the organic carrier becomes a transparent and uniform liquid. After the liquid cools to room temperature, add the coupling agent, continue stirring for 5 minutes, vacuum remove bubbles and bottle for later use.

[0175] (2) Preparation of conductive silver paste

[0176] 300nm~2μm nano-sized spherical silver powder, 5~10μm spherical silver powder and 20~30μm spherical silver powder are compounded and weighed in a metal stacking method at a ratio of 9:17:74. First, 1g of the binder is weighed with an electronic analytical balance and added into a beaker. Then, the prepared organic carrier is added and stirred in a constant temperature water bath of 60°C to obtain a resin solution. Finally, the three silver powders prepared above are added to the resin solution in order from small to large in size, and placed in a high-speed disperser for high-speed dispersion at 1500r / min for 2~3 hours. After being dispersed evenly, the prepared conductive silver paste is obtained.

[0177] Comparative Example 2

[0178] Prepare the required raw materials according to the following weight ratios

[0179] A. Spherical silver powder with particle size of 300nm~2μm: 2.975g

[0180] B. Spherical silver powder with particle size of 5-10 μm: 5.525 g

[0181] C. Spherical silver powder with a particle size of 20 to 30 μm: 24.05 g

[0182] D. Organic solvent with boiling range of 120-140°C: 11.475 g

[0183] E. Additives: leveling agent 0.135g, defoaming agent 0.135g, thixotropic agent 1.08g

[0184] F. Thickener: 0.675g

[0185] G. Coupling agent: 2g

[0186] H. Binder: 1g

[0187] Wherein, the organic solvent is diethyl carbonate.

[0188] Among them, the leveling agent is BYK-381, the defoaming agent is BYK-A530, the thixotropic agent is BYK-410, and the thickener is ethyl cellulose.

[0189] Among them, the coupling agent is KH560.

[0190] Wherein, the adhesive is epoxy resin E51.

[0191] The specific preparation method is carried out according to the following steps:

[0192] (1) Preparation of organic carrier

[0193] Use an electronic analytical balance to weigh 11.475g of organic solvent diethyl carbonate and 0.675g of thickener ethyl cellulose in a ratio of 17:1 and put them into a beaker. Stir in a constant temperature 60℃ water bath until the thickener is completely dissolved. Then add the leveling agent, defoamer, and thixotropic agent into the beaker in a ratio of 1:1:8, keep stirring in a constant temperature water bath at 60℃ for 2 to 3 hours until the organic carrier becomes a transparent and uniform liquid. After the liquid cools to room temperature, add the coupling agent, continue stirring for 5 minutes, vacuum remove bubbles and bottle for later use.

[0194] (3) Preparation of conductive silver paste

[0195] 300nm~2μm nano-sized spherical silver powder, 5~10μm spherical silver powder and 20~30μm spherical silver powder are compounded and weighed in a metal stacking method at a ratio of 9:17:74. First, 1.0g of epoxy resin E51 is weighed with an electronic analytical balance and added to a beaker. Then, the prepared organic carrier is added and stirred in a constant temperature water bath of 60°C to obtain a resin solution. Finally, the three silver powders prepared above are added to the resin solution in order from small to large in size, and placed in a high-speed disperser for high-speed dispersion at 1500r / min for 2~3 hours. After being dispersed evenly, the prepared conductive silver paste is obtained.

[0196] Comparative Example 3

[0197] Prepare the required raw materials according to the following weight ratio:

[0198] A. Spherical silver powder with particle size of 300nm~2μm: 2.925g

[0199] B. Spherical silver powder with particle size of 5-10 μm: 5.525 g

[0200] C. Spherical silver powder with a particle size of 20 to 30 μm: 24.05 g

[0201] D. Organic solvent with boiling range of 120℃~140℃: 11.475g

[0202] E. Additives: leveling agent 0.135g, defoaming agent 0.135g, thixotropic agent 1.08g

[0203] F. Thickener: 0.675g

[0204] G. Coupling agent: 2g

[0205] H. Binder: 1g

[0206] Wherein, the organic solvent is diethyl carbonate.

[0207] Among them, the leveling agent is BYK-381, the defoaming agent is BYK-A530, the thixotropic agent is BYK-410, and the thickener is ethyl cellulose.

[0208] Among them, the coupling agent is KH560.

[0209] The binder is a mixture of cardanol-based epoxy resin and epoxy resin E51 in a mass ratio of 2:3.

[0210] The specific preparation method is carried out according to the following steps:

[0211] (1) Preparation of organic carrier

[0212] Use an electronic analytical balance to weigh 11.475g of organic solvent diethyl carbonate and 0.675g of thickener ethyl cellulose in a ratio of 17:1 and put them into a beaker. Stir in a constant temperature 60℃ water bath until the thickener is completely dissolved. Then add the leveling agent, defoamer, and thixotropic agent into the beaker in a ratio of 1:1:8, keep stirring in a constant temperature water bath at 60℃ for 2 to 3 hours until the organic carrier becomes a transparent and uniform liquid. After the liquid cools to room temperature, add the coupling agent, continue stirring for 5 minutes, vacuum remove bubbles and bottle for later use.

[0213] (2) Preparation of conductive silver paste

[0214] 300nm-2μm nano-sized spherical silver powder, 5-10μm spherical silver powder and 20-30μm spherical silver powder were weighed in a metal stacking manner at a ratio of 9:17:74. First, 1g of the binder was weighed with an electronic analytical balance and added to a beaker. Then, the prepared organic carrier was added and stirred in a constant temperature 60°C water bath to obtain a resin solution. Finally, the three silver powders prepared above were randomly added to the resin solution without order of size, placed in a high-speed disperser for high-speed dispersion at 1500r / min for 2-3 hours, and dispersed evenly to obtain a prepared conductive silver paste. This comparative example was not added in order of silver powder particle size, and was used to verify the anti-settling effect of nano silver powder.

[0215] The present invention uses Examples 1 to 6 and Comparative Examples 1 to 3 to prepare the conductive silver paste, uses a PI film as a substrate, and uses a four-sided preparation device to perform a scraping-treatment, and performs a series of characterizations such as optics, SEM, resistivity, and density.

[0216] The present invention first measures the density of the conductive silver paste after curing, and uses the water displacement method to determine the density. The specific method is as follows: the mass m of the silver paste after curing is measured, and then it is placed in a measuring cylinder filled with a certain volume of water, and the volume v of the changed water is measured. The final density of the silver paste is measured by the density formula of the water displacement method, and the result is as follows:

[0217] The density results of the conductive silver paste (prepared by the method described in Example 2) with a curing temperature of 126° C. and a binder resin of 1 g, which is a mixture of epoxy resin E51 and carbophenol epoxy resin in a ratio of 3:2, are shown in Table 1.

[0218] Table 1 Density results of the conductive silver paste prepared in Example 2

[0219]

[0220] The density results of the conductive silver paste (prepared by the method described in Example 3) with a curing temperature of 126° C. and a resin of 1 g, which is a mixture of epoxy resin E51 and carbophenol epoxy resin in a ratio of 7:3, are shown in Table 2.

[0221] Table 2 Density results of the conductive silver paste prepared in Example 3

[0222]

[0223] The density results of the conductive silver paste (prepared by the method described in Comparative Example 2) with a curing temperature of 126° C. and 1 g of resin, which is epoxy resin E51, are shown in Table 3.

[0224] Table 3 Density results of the conductive silver paste prepared in Comparative Example 2

[0225]

[0226] The curing temperature is 180°C, the sample raw material is purchased conductive silver paste (purchased from Suyin Electronic Materials Co., Ltd., 8000b-H75 conductive silver paste), the silver powder morphology size is 6-10μm, and the density results of 50nm thick flake silver powder are shown in Table 4.

[0227] Table 4 Density results of commercial conductive silver paste

[0228]

[0229] The present invention also tests the bending resistance of the conductive silver paste after curing. The test steps for the bending resistance test are as follows: first use a four-probe tester to test the resistivity at the center of the line, and the obtained resistivity is recorded as the resistivity before the test ρ0; fold the line 180° in the middle, apply pressure at the fold line with a 2kg weight and hold for 1 minute, then fold the line 180° in the opposite direction and apply pressure for the same length of time; repeat the above two steps 10 times in total, and finally use a four-probe tester to test the resistivity at the center of the line after bending, and record it as the resistivity after the test ρ. The bending resistance of the sample is characterized by the resistivity change rate before and after the test,

[0230] The resistivity change rate calculation formula is as follows:

[0231]

[0232] in is the resistivity change rate before and after the test, ρ is the resistivity after the test, and ρ0 is the resistivity before the test. The test results are as follows:

[0233] The curing temperature is 126° C., the resin is 1 g, and the anti-bending properties of the conductive silver paste (prepared by the method described in Example 2) which is a mixture of epoxy resin E51 and cardanol-based epoxy resin in a ratio of 3:2 are shown in Table 5.

[0234] Table 5 Anti-bending performance of the conductive silver paste prepared in Example 2

[0235]

[0236] The curing temperature is 126° C., the resin is 1 g, and the anti-bending properties of the conductive silver paste (prepared by the method described in Example 3) which is a mixture of epoxy resin E51 and cardanol-based epoxy resin in a ratio of 7:3 are shown in Table 6.

[0237] Table 6 Anti-bending performance of the conductive silver paste prepared in Example 3

[0238]

[0239] The curing temperature is 126° C., the resin is 1 g, and the anti-bending properties of the conductive silver paste (prepared by the method described in Comparative Example 2) of epoxy resin E51 are shown in Table 7.

[0240] Table 7 Anti-bending performance of the conductive silver paste prepared in Comparative Example 2

[0241]

[0242] The curing temperature is 180°C, the sample raw material is purchased conductive silver paste (purchased from Suyin Electronic Materials Co., Ltd., 8000b-H75 conductive silver paste), the silver powder morphology size is 6-10μm, and the bending resistance of 50nm thick flake silver powder is shown in Table 8.

[0243] Table 8 Anti-bending properties of commercial conductive silver paste

[0244]

[0245] In order to study the specific effects of the presence of cardanol-based epoxy resin and its addition amount on the mechanical properties of conductive silver paste, the present invention conducted an anti-bending performance test, and the relevant data are summarized in Tables 5-8. After careful analysis of the test results, the following conclusions can be drawn: After adding cardanol-based epoxy resin to the conductive silver paste, its anti-bending performance has been significantly improved. In particular, when the ratio of epoxy resin E51 to cardanol-based epoxy resin is 3:2, the anti-bending performance of the conductive silver paste reaches the best. In contrast, the conductive silver paste without the addition of cardanol-based epoxy resin and the conductive silver paste purchased directly on the market performed poorly in anti-bending performance.

[0246] The present invention measures the resistivity of the conductive silver paste after curing. After the prepared conductive silver paste is cured, it is scraped using a four-sided preparation device or screen printing, evenly coated on the PI substrate, and scraped out films of different thicknesses. A four-probe tester is used to accurately measure the resistivity of the sample. The specific results are as follows:

[0247] The resistivity results of the conductive silver paste (prepared by the method described in Example 2) with a curing temperature of 126° C. and a resin of 1 g, which is a mixture of epoxy resin E51 and cardanol-based epoxy resin in a ratio of 3:2, are shown in Table 9.

[0248] Table 9 Resistivity results of the conductive silver paste prepared in Example 2

[0249]

[0250] The resistivity results of the conductive silver paste (prepared by the method described in Example 3) with a curing temperature of 126° C. and a resin of 1 g, which is a mixture of epoxy resin E51 and cardanol-based epoxy resin in a ratio of 7:3, are shown in Table 10.

[0251] Table 10 Resistivity results of the conductive silver paste prepared in Example 3

[0252]

[0253] The resistivity results of the conductive silver paste (prepared by the method described in Comparative Example 2) with a curing temperature of 126° C. and 1 g of the resin being epoxy resin E51 are shown in Table 11.

[0254] Table 11 Resistivity results of the conductive silver paste prepared in Comparative Example 2

[0255]

[0256]

[0257] The resistivity results of the conductive silver paste with a curing temperature of 126°C, a resin 1g with a mass ratio of E51:cardanol of 7:3, and a ratio of the three silver powders of 15:11:74 are shown in Table 12.

[0258] Table 12 Resistivity results of the conductive silver paste prepared in Example 5

[0259]

[0260] The curing temperature is 180°C, the sample raw material is purchased conductive silver paste (purchased from Suyin Electronic Materials Co., Ltd., 8000b-H75 conductive silver paste), the silver powder morphology size is 6-10μm, and the resistivity results of 50nm thick flake silver powder are shown in Table 13.

[0261] Table 13 Resistivity results of commercial conductive silver paste

[0262]

[0263]

[0264] In order to further explore the specific effects of the two variables, the amount of cardanol-based epoxy resin added and the non-optimal metal stacking method, on the performance of the conductive silver paste, the present invention performed resistivity tests and systematically organized the obtained data in Tables 9 to 13. After detailed testing and data analysis, the following conclusions were drawn:

[0265] When the amount of cardanol-based epoxy resin added makes the mechanical properties of the conductive silver paste reach the optimal state, its resistivity test results are also excellent. This excellent performance is attributed to the lower viscosity of cardanol-based epoxy resin compared to epoxy resin E51. As the amount of E51 is reduced, the viscosity of the entire system also decreases, which leads to a reduction in the gap between the silver powder particles inside the silver paste, thereby effectively reducing the resistivity.

[0266] On the other hand, when the three non-optimal silver powder metal stacking methods are used, the resistivity of the resulting conductive silver paste is relatively high. This result is not only higher than the conductive silver paste purchased directly on the market, but also higher than the conductive silver paste prepared by our optimal silver powder ratio. This comparison further highlights the important role of metal stacking methods and the amount of cardanol-based epoxy resin added in regulating the resistivity of conductive silver paste.

[0267] The present invention provides a high-density, low-temperature curing conductive silver paste and a method for preparing the same. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be considered as the scope of protection of the present invention. All components not specified in this embodiment can be implemented using existing technologies.

Claims

1. A high-density, low-temperature curing conductive silver paste, characterized in that: The invention comprises the following components in proportion by weight: A. Spherical silver powder with a particle size of 300nm to 2μm: 5 to 15 parts; B. Spherical silver powder with a particle size of 5 to 10 μm: 10 to 25 parts; C. Spherical silver powder with a particle size of 20 to 30 μm: 30 to 50 parts; D. Organic solvent: 15 to 30 parts; E. Additives: 0.1 to 3 parts of leveling agent, 0.1 to 3 parts of defoaming agent, 1 to 3 parts of thixotropic agent; F. Thickener: 1 to 3 parts; G. Coupling agent: 1 to 5 parts; H. Binder: 1 to 5 parts.

2. The high-density, low-temperature curing conductive silver paste according to claim 1, characterized in that: The weight ratio of the spherical silver powder with a particle size of 300nm to 2μm, the spherical silver powder with a particle size of 5 to 10μm and the spherical silver powder with a particle size of 20 to 30μm is 1:1 to 2:1 to 9, preferably 9:17:

74.

3. The high-density, low-temperature curing conductive silver paste according to claim 1, characterized in that: The binder comprises cardanol-based epoxy resin, and the mass percentage of the cardanol-based epoxy resin in the binder is 20% to 50%.

4. The high-density, low-temperature curing conductive silver paste according to claim 3, characterized in that: The adhesive further comprises a mixture of any one or more of epoxy resin E51, acrylic resin, polyamino resin, epoxy-modified polyester resin, epoxy polyphenol resin or polyurethane resin; preferably epoxy resin E51.

5. The high-density, low-temperature curing conductive silver paste according to claim 1, characterized in that: The organic solvent has a boiling range of 120-140° C. and is preferably a mixture of any one or more of butyl acetate, ethylene glycol methyl ether, propylene glycol methyl ether acetate, diethyl carbonate, cyclohexanone, 4-methyl-2-pentanone and ethylene glycol ethyl ether acetate.

6. The high-density, low-temperature curing conductive silver paste according to claim 1, characterized in that: The leveling agent is a mixture of any one or more of polydimethylsiloxane, BYK-381 and polyacrylate; The defoamer is BYK-A530 or polyether-modified siloxane, or a mixture of the two; The thixotropic agent is BYK-410.

7. The high-density, low-temperature curing conductive silver paste according to claim 1, characterized in that: The thickener is a mixture of any one or more of ethyl cellulose, polyvinyl alcohol, epoxy resin E51, polyvinyl butyral ester and polyisobutylene; The coupling agent is a mixture of any one or more of KH550, KH560, KH570, KH792 and DL602.

8. The high-density, low-temperature curing conductive silver paste according to any one of claims 1 to 7, characterized in that: The high density is 2.3-3 g / cm 3 ; The low temperature curing, the curing temperature is 120 ~ 140 ℃.

9. The method for preparing the high-density, low-temperature curing conductive silver paste according to any one of claims 1 to 7, characterized in that: The steps include: (1) Preparation of organic carrier solution: After fully mixing the organic solvent and thickener in the formula amount, adding the auxiliary agent and mixing evenly, and then adding the coupling agent to obtain the organic carrier solution; (2) Preparation of conductive silver paste: Add a binder to the organic carrier solution and mix well to obtain a resin solution, add spherical silver powder to the resin solution in order of particle size, and disperse at high speed to obtain a conductive silver paste.

10. The preparation method according to claim 9, characterized in that: In step (1), the organic solvent and the thickener are mixed and stirred at 50-90° C. until the thickener is completely dissolved; after adding the auxiliary agent, stir at 40-80° C. for 1.5-4 hours; In step (2), the binder is added to the organic carrier solution and then stirred at 50-80° C. to mix evenly; the high-speed dispersion is performed at a rotation speed of 1000-1200 rpm for a time of 0.5-3 h.

Citation Information

Cited By

  • Wear-resistant environment-friendly conductive silver paste and preparation method thereof

    CN120878354A

  • A wear-resistant and environmentally friendly conductive silver paste and its preparation method

    CN120878354B

  • Environment-friendly low-odor stretchable conductive silver paste and preparation method and application thereof

    CN121439321A

  • Environment-friendly low-odor stretchable conductive silver paste, preparation method and application thereof

    CN121439321B